The Effect of Perceived Quality and Brand Image on Smartphone Purchase Decisions - Maheirina Disman; Nurdin Batjo; Akbar Sabani (Dinamis : Journal of Islamic Management and Bussiness, 2022)
This thesis discusses the Influence of Perceived Quality and Brand Image on Smartphone Purchase Decisions. This study aims to determine the effect of perceived quality and brand image on smartphone purchase decisions. This type of research uses a quantitative approach. This research was carried out by distributing questionnaires to 150 respondents. The classical assumption tests used in this study include the normality test, multicollinearity test, heteroscedasticity test and linearity test. The hypothesis testing includes the T test (ParsiaI), F test (SimuItan) and the Determination Coefficient Test. The research results show that there is a partial significant effect on perceived quality (X1) on smartphone purchase decisions (Y), this is evidenced by the obtained results of a significance value of (sig) 0.000 < (α) 0.05, so that H0 is rejected and H1 is accepted . There is a partial significant effect of brand image (X2) on the purchase decision (Y) of a smartphone, this is evidenced by the acquisition of a significance value of (sig) 0.001 < (α) 0.05. So that H0 is rejected and H1 is accepted. Perceived quality (X1) and brand image (X2) simultaneously (together) have a significant effect on the decision to purchase (Y) smartphone, amounting to 0.000 <0.05 and f value 36,897 > t table value 3.06 this proves that H0 is rejected and H1 is accepted, this is also shown in the R square value of 0.334 this means that the simultaneous effect of variables X1 and X2 on variable Y is 33.4%, the remaining 66.6% is explained by other variables not discussed in this study.